Water rights in Southeast Asia and India - Pink, Ross Michael 1959- (Palgrave Macmillan, 2016)
"Examines the foremost human rights issue of the twenty-first century: clean drinking water. Dynamic and vital water issues are explored in nine countries: Burma/Myanmar, Cambodia, China, India, Indonesia, Laos, the Philippines, Thailand, and Vietnam. 800 million people today have no clean water sources. This number will soar to over two billion by 2050 because of pollution, surging population in the developing world, and climate change, which will accelerate drought, flooding, and disease. The global community has a historic and epic task to establish innovative and sustainable practices at both the international and village level to safeguard the precious human right to water for billions of citizens"...